Veno-venous ECMO-assisted orthopedic stabilization for polytrauma with severe ARDS and refractory hypoxemia: a case report - Liu, Lin; Deng, Kaiji; Tang, Haifeng; Wang, Yanjun (Frontiers in Medicine, 2026)
This case report describes the successful integration of veno-venous extracorporeal membrane oxygenation (VV-ECMO) with physiologically optimized fracture fixation in a critically ill polytrauma patient who presented with life-threatening acute respiratory distress syndrome (ARDS). A 23-year-old male with bilateral femoral fractures, Gustilo IIIB open tibiofibular injury, left radius-ulna fractures, and refractory hypoxemia (PaO2/FiO2 40.5 mm Hg) underwent VV-ECMO initiation 1 h postinjury (total ECMO duration 144 h). Physiological optimization guided delayed surgical intervention on day 5, incorporating heparin-based anticoagulation and dynamic ECMO parameter modulation, resolving lactic acidosis (peak lactate 5.0 mmol/L on day 1 to 1.8 mmol/L preoperatively). The patient achieved successful decannulation by day 6 with satisfactory recovery at the 2-month follow-up [Short Musculoskeletal Function Assessment (SMFA) score 28.1, gait speed 1.2 m/s]. This case demonstrates the feasibility of a multidisciplinary protocol challenging traditional contraindications to surgery in severe ARDS patients and providing a replicable protocol for managing competing priorities of oxygenation and hemorrhage control.